Penerapan Pendekatan TaRL untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik di UPT SMP Negeri 8 Medan - Winny Thesa Sianturi; Siti Nurjannah; Rosliana Siregar; Ratna Soraya (Journal on Education, 2024)
The research aims to increase the motivation and learning outcomes of students at UPT SMP Negeri 8 Medan by implementing the Teaching at Right Level (TaRL) approach. The subjects in this research were 30 students in class VIII-2 UPT SMP Negeri 8 Medan. This research is classroom action research carried out in 2 cycles. The two cycles carried out 4 learning meetings and 2 evaluations. The results of the research show that students' learning motivation has increased, in the pre-cycle the average was 65.2 in the sufficient category, then in the first cycle it increased to 74.9 in the sufficient category. In cycle II, the average learning motivation of students increased to 83.3 in the good category, while for learning outcomes there was an increase in classical completeness in the pre-cycle by 20%, then in cycle I it increased to 50%, improvements were made in cycle II, classical completeness was the result student learning increased to 87%. So, it can be concluded that implementing the TaRL approach can increase student motivation and learning outcomes at UPT SMP Negeri 8 Medan.